Maqonqo Shelter: the excavation of Holocene deposits in the eastern Biggarsberg, Thukela Basin, South Africa - Mazel, A. D. (Southern African Humanities, 2021)
The excavation of Maqonqo Shelter in the eastern Biggarsberg, Thukela Basin, is reported. The lithic and non-lithic cultural, faunal and floral assemblages recovered during excavations are presented. The site experienced three phases of occupation. The initial occupation dates back to the Middle Stone Age, but the deposits relating to this period have not been excavated. The second, and primary, occupation occurred during the early and mid Holocene. The third occupation was an ephemeral second millennium AD occupation, and may have been by hunter-gatherers, agriculturists or both. Despite problems associated with the post-depositional vertical displacement of cultural and subsistence remains, examination of the material recovered from Maqonqo has generated new insights into Thukela Basin hunter-gatherer history. The eastern Biggarsberg has been identified as the focus of Thukela Basin hunter-gatherer settlement during the early Holocene. I propose that Thukela Basin hunter-gatherers experienced four, and not three phases of social structural development between 10000 and 2000 b.p. as previously suggested. The additional phase relates to the early Holocene occupation of the eastern Biggarsberg.